Due diligence and valuation of mineral assets for debt financing: practitioner’s perspectives - Gambiza, William (My University, 2022)
The metal and mining industry has remained one of the major sectors in need of finance from credit institutions in Zimbabwe. The performance of Zimbabwe mining loan books however is very poor as the non-performing loans are averaging 20% against an industry target of 5%. The high number of non-performance mining loans has caused most banks and creditors to withdraw due to poor return on investment. Minimal participation by banks and other credit institutions has resulted in the mining sector being under-capitalised for years. The Chamber of Mines of Zimbabwe has estimated that the mining industry requires over US$5 billion in the next five years for various reasons namely: exploration, developing new mines, opening closed mines, and increasing installed capacities. The presence of high non-performing mining loans prompted the researcher to conduct a study to come up with a due diligence and valuation framework that practitioners can use when dealing with the metals and mining sector. The researcher also aims at establishing whether the banking sector acknowledges the importance of mine due diligence and valuations and the skills required to undertake this exercise. To undertake the exercise, thirty-five closed-ended questionnaires were distributed to the target population, five structured interviews were conducted with executives, and focus group discussions were done with personnel with mining finance experience. All participants pointed out that mine due diligence and valuation is an important step in investment finance. The participants also pointed out that the due diligence should consist of mining experts, metallurgists, geologists, legal experts, environmental experts as well as competent mineral asset valuators. Although the participants pointed out these issues, executives indicated that banks do not have the skills required to undertake due diligence and valuation of mineral assets which results in deal structuring risk which is one of the main reasons why mining loan books have high non-performing loans. Based on these findings, the researcher strongly recommends mining schools in Zimbabwe start offering courses in mine due diligence and valuation. Banks should also outsource the required skills from the region and should also consider legal experts and human resources experts as key members of the mine due diligence team.
A research report was submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Science in Engineering, 2022